2017
DOI: 10.1007/s11060-017-2410-3
|View full text |Cite
|
Sign up to set email alerts
|

Can anti-vascular endothelial growth factor antibody reverse radiation necrosis? A preclinical investigation

Abstract: Anti-vascular endothelial growth factor (anti-VEGF) antibodies are a promising new treatment for late time-to-onset radiation-induced necrosis (RN). We sought to evaluate and validate the response to anti-VEGF antibody in a mouse model of RN. Mice were irradiated with the Leksell Gamma Knife PerfexionTM and then treated with anti-VEGF antibody, beginning at post-irradiation (PIR) week 8. RN progression was monitored via anatomic and diffusion MRI from weeks 4 to 12 PIR. Standard histology, using haematoxylin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Nonirradiated glioblastoma tumor cells (DBT) were implanted in the ipsilateral hemisphere 6 weeks postirradiation (13). Anatomic MRI and histology (hemotoxylin and eosin [H&E] staining) showed no evidence of frank radiation necrosis or structural changes at these irradiation doses (14, 15). (We note that laboratory mice are roughly half as radiation sensitive [re LD 50 ] as humans.…”
Section: Methodsmentioning
confidence: 99%
“…Nonirradiated glioblastoma tumor cells (DBT) were implanted in the ipsilateral hemisphere 6 weeks postirradiation (13). Anatomic MRI and histology (hemotoxylin and eosin [H&E] staining) showed no evidence of frank radiation necrosis or structural changes at these irradiation doses (14, 15). (We note that laboratory mice are roughly half as radiation sensitive [re LD 50 ] as humans.…”
Section: Methodsmentioning
confidence: 99%
“…We have developed a novel, Gamma Knife ® (GK) enabled, focal (hemispheric) brain-irradiation mouse model ( 10 ), termed the Radiation-Induced Immunosuppressive Microenvironment (RI 2 M) model, that provides a powerful platform for investigation into the late effects of irradiation on the brain parenchyma microenvironment. Earlier studies of GK-enabled focal-irradiation of mouse brain from this laboratory employed substantially greater radiation doses and were purposefully designed to reliably elicit late-time-to-onset radiation necrosis in an experimentally tractable time frame, with radiation necrosis consistently appearing approximately four to eight weeks post-irradiation ( 11 17 ). Importantly, the resultant radiation necrosis in the mouse brain recapitulated all of the key histologic hallmarks of the clinically observed pathology, giving strong confidence regarding the platform’s clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, VEGF expression inhibitor bevacizumab (AvastinV R , Genentech) has been used to treat radiation-induced brain necrosis in 15 patients (Gonzalez et al 2007), and has efficiently decreased it in 50-60 Gy gamma ray ('gamma knife' model) irradiated mice . However, bevacizumab treatment has been reported to cause side effects during prolonged administration, including vessel overpruning, deep vein thrombosis and focal mineralization (Jeyaretna et al 2011;Levin et al 2011;Duan et al 2017). Moreover, other studies have demonstrated the recurrence of radiation necrosis after stopping bevacizumab treatment and drugresistance for re-treatment after discontinuation (Furuse et al 2011;Zhuang et al 2016).…”
Section: Reducing Inflammationmentioning
confidence: 99%